2014
DOI: 10.1371/journal.pgen.1004131
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Models of Apoptosis-Induced Proliferation Decipher Activation of JNK and Identify a Requirement of EGFR Signaling for Tissue Regenerative Responses in Drosophila

Abstract: Recent work in several model organisms has revealed that apoptotic cells are able to stimulate neighboring surviving cells to undergo additional proliferation, a phenomenon termed apoptosis-induced proliferation. This process depends critically on apoptotic caspases such as Dronc, the Caspase-9 ortholog in Drosophila, and may have important implications for tumorigenesis. While it is known that Dronc can induce the activity of Jun N-terminal kinase (JNK) for apoptosis-induced proliferation, the mechanistic det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(169 citation statements)
references
References 95 publications
6
162
0
Order By: Relevance
“…This system creates a condition of dying/undead cells flanked by apoptosis-induced cell proliferation of normal cells. Although JNK is activated in apoptotic as well as adjacent surviving cells, it has been shown that the identification of upstream and downstream signaling pathways is much dependent on the apoptosis-inducing system used (47). Hence, the complex tissue heterogeneity created by local cell death seems to obscure a straightforward dissection of the required signaling cascades during normal regeneration.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tomentioning
confidence: 99%
“…This system creates a condition of dying/undead cells flanked by apoptosis-induced cell proliferation of normal cells. Although JNK is activated in apoptotic as well as adjacent surviving cells, it has been shown that the identification of upstream and downstream signaling pathways is much dependent on the apoptosis-inducing system used (47). Hence, the complex tissue heterogeneity created by local cell death seems to obscure a straightforward dissection of the required signaling cascades during normal regeneration.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tomentioning
confidence: 99%
“…It is not known whether yki is activated during engulfment, or what role this might play if so, but both JNK and Yki have been implicated in compensatory proliferation in response to cell death (Ryoo et al 2004;Worley et al 2012). The role of JNK in compensatory proliferation was presumed to occur in the apoptotic cells, perhaps in the generation of proliferative signals from dying cells, but recently activity in the compensating cells has also been demonstrated (Fan et al 2014). This would be consistent with a signal for compensatory proliferation being sent to JNK and Yki when Drpr recognizes apoptotic cells.…”
Section: Conclusion and Modelmentioning
confidence: 99%
“…AiP in Drosophila channels through the apoptotic machinery, where Dronc/Caspase-9 activates a feedback loop involving JNK and p53. 2,3 However, the underlying mechanisms of AiP lack apparent molecular details. It has been proposed that the molecular mechanisms that distinguish between apoptosis and AiP may rely on specific p53 isoforms (Dp53 or DDNp53 expression, 4 Fig.…”
Section: Cell Cycle News and Viewsmentioning
confidence: 99%